Keluarga sebagai Communio Personarum di Zaman Modern dalam Terang Familiaris Consortio - Yosef Gunawan; Felix Riondi Sugar; Marselinus Langgor; Yoseph Taus; Protasius Karsa; Eugenius Gefron Dalu; Yanuarius Kaprio Anfilgo; Martinus Dampul (STIKAS Santo Yohanes Salib Kalimantan Barat, 2026)
The modern era has brought significant changes to human life, including to family structures and relationships. The dominance of individualism and materialism, as well as the development of digital technology, has affected the quality of interpersonal relationships within families. This paper aims to analyse the family as communio personarum in the modern era, based on the teachings of Familiaris Consortio. The research method used was qualitative research with a descriptive-analytical approach through a literature study of Church documents, particularly Familiaris Consortio, as well as theological literature on family and related scientific literature. The results of the study show that the family as Ecclesia Domestica is called to live out a communion of persons rooted in Trinitarian love. However, the modern reality reveals serious challenges in the form of individualism, work commitments, and technological dependency, which reduce the quality of family relationships. Therefore, an updated understanding and practice of communio personarum is required to ensure that the family remains an authentic and relevant community of love in the modern era.